Autism: Historic View and a Current Biomedical Engineering Approach [Retrospectroscope] - Pérez Berenguer, María Elisa (2015)
This paper presents a software specially designed for children with autism spectrum disorder (ASD) and its evaluation with a selected group of patients. The software is simple, easy to manage, and with a friendly interface; it has activities that stimulate the cognitive and motor development. The Fitt´s law and the Scale Usability System were used to evaluate the performance of the software, carried out with a group of children suffering ASD that attend phonoaudiology therapies at the state hospital. The results are very encouraging because the children were interested using the software and also the evaluation tests allow the quantification of the performance, showing better coefficients with the SicaaKids environment than with the Windows® desktop.